Fission impossible (?) - new insights into disorders of peroxisome dynamics - Carmichael, Ruth E.; Islinger, Markus; Schrader, Michael (Cells, 2022)
Peroxisomes are highly dynamic and responsive organelles, which can adjust their morphology, number, intracellular position, and metabolic functions according to cellular needs. Peroxisome multiplication in mammalian cells involves the concerted action of the membrane-shaping protein PEX11β and division proteins, such as the membrane adaptors FIS1 and MFF, which recruit the fission GTPase DRP1 to the peroxisomal membrane. The latter proteins are also involved in mitochondrial division. Patients with loss of DRP1, MFF or PEX11β function have been identified, showing abnormalities in peroxisomal (and, for the shared proteins, mitochondrial) dynamics as well as developmental and neurological defects, whereas the metabolic functions of the organelles are often unaffected. Here, we provide a timely update on peroxisomal membrane dynamics with a particular focus on peroxisome formation by membrane growth and division. We address the function of PEX11β in these processes, as well as the role of peroxisome-ER contacts in lipid transfer for peroxisomal membrane expansion. Furthermore, we summarize the clinical phenotypes and pathophysiology of patients with defects in the key division proteins DRP1, MFF, and PEX11β as well as in the peroxisome-ER tether ACBD5. Potential therapeutic strategies for these rare disorders with limited treatment options are discussed.
Gesehen am 09.01.2024
Im Titel ist das Fragezeichen in Klammern geschrieben
Dieser Artikel gehört zum Special issue: Peroxisomal disorders: development of targeted therapies